Factors Related to Domestic Violence against Female Employees in Educational Hospitals Affiliated to Isfahan University of Medical Sciences in 2016 - Hojat Sheikhbardsiri; GHolamreza Khademipour; Mohsen Aminizadeh; Roholallah Fatemian; Mohammad Mahdi Doustmohammadi (Tehran University of Medical Sciences, 2018)
Background: Physical and verbal violence against hospital personnel is very critical problems that could influence the quality of clinical and nursing cares. Today, problem prevention and identification of related factors with domestic violence against women have been considered as a health priority in many countries. Therefore, due to the importance of this issue, this study aimed to determine related factors with domestic violence against women in educational hospitals affiliated to Isfahan University of Medical Sciences.   Materials and Methods: This cross-sectional study was a descriptive-analytical one which conducted on 836 female employees using census method. Data collection performed using a researcher-made questionnaire. This questionnaire consisted of 34 items in four dimensions (physical, verbal and mental, sexual) and violence experienced by the husband. Data were analyzed using SPSS version 16 with descriptive statistics and analytic statistics such as Kolmogorov-Smirnov, ANOVA, independent t test, and Pearson correlation coefficient and multivariate regression.   Results: Study results revealed that verbal and mental (55.33%), physical (36.16%), and sexual (6.66%) violence were the most common type of violence against women, respectively. There was a significant statistically association between age gap, forced marriage, husband's addiction, income and precedent violence Experience and violence against women.   Conclusion: This study presented prevalence and related factors of demotic violence among women. Therefore, it is imperative that health authorities, especially hospital managers, pay attention to this phenomenon assessing further investigation of factors related to violence against women in order to take the necessary steps to mitigate and reduce related factors using life skills workshop, training and counseling for couples.